What is the value of retail order flow? - Peter Hoffmann; Stephan Jank (Deutsche Bundesbank, 2024)
This paper uses regulatory data to assess the value of retail order flow in the German equity market. To this end, we examine the performance of specialized retail market makers (RMMs) that internalize a large share of retail activity via affiliated trading venues. We show that retail market making is extremely profitable, with an average (gross) Sharpe ratio of 17.85, which is more than twice as large as that earned by proprietary trading firms (PTFs) active in public limit order markets. A simple calculation suggest that RMMs would be willing to give up around 60% of their revenues, or 1.76 bps of their trading volume, for access to retail order flow. The profitability of retail market making is rooted in reduced exposure to adverse selection and inventory risk.
Keywords: G10; G12; 330; Equity markets; retail trading; market making; internalization; payment for order flow